2022
DOI: 10.3389/fimmu.2021.768560
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Pathway Metabolites as Potential Clinical Biomarkers in Coronary Artery Disease

Abstract: Coronary artery disease (CAD) is one of the leading cause of mortality worldwide. Several risk factors including unhealthy lifestyle, genetic background, obesity, diabetes, hypercholesterolemia, hypertension, smoking, age, etc. contribute to the development of coronary atherosclerosis and subsequent coronary artery disease. Inflammation plays an important role in coronary artery disease development and progression. Pro-inflammatory signals promote the degradation of tryptophan via the kynurenine pathway result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 149 publications
(222 reference statements)
1
14
0
4
Order By: Relevance
“…The role of the kynurenine pathway in atherosclerotic disease has been extensively reviewed [113][114][115]. A state of low-grade inflammation in atherosclerosis is marked by increased levels of IL-6, an inducer of IDO [116].…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the kynurenine pathway in atherosclerotic disease has been extensively reviewed [113][114][115]. A state of low-grade inflammation in atherosclerosis is marked by increased levels of IL-6, an inducer of IDO [116].…”
Section: Atherosclerosismentioning
confidence: 99%
“…A state of low-grade inflammation in atherosclerosis is marked by increased levels of IL-6, an inducer of IDO [116]. Once more, research shows that decreased tryptophan and an increased kynurenine/tryptophan-ratio is associated with the severity of atherosclerosis [113] and thus indicating that increased IDO-activity is related to this state of low-grade inflammation.…”
Section: Atherosclerosismentioning
confidence: 99%
“…Воспаление, по-видимому, является одним из основных катализаторов переключения с синтеза серотонина на кинурениновый путь, поскольку провоспалительные цитокины индуцируют активность ферментов идоламин 2,3-диоксигеназы (IDO) и триптофан 2,3-диоксигеназы (TDO), которая обычно низкая в базальных условиях [15]. Несбалансированный кинуреновый путь вовлечен в патомеханизмы различных заболеваний, включая ишемическую болезнь сердца [16].…”
Section: Conflicts Of Interestsunclassified
“…Besides, the ratio of KYN/TRP may a sensitive pointer of rigorous coronary events for individuals displaying no history of CHD, also can be used to predict dangerous coronary events even use to determining all-cause mortality for individuals suffering from CHD ( Pedersen et al, 2011 ; Sulo et al, 2013 ). Additionally, a new review of more than 20 clinical studies also shown that the change of other TRP metabolites/TRP ratio also predict the significant CHD, so TRP pathway metabolites may as potential clinical biomarkers in CHD ( Gáspár et al, 2021 ). Our previous plasma metabolome and genome-wide association studies also found that IPA may have a potential protective effect on patients with CHD ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%